A survey of single and multi-component Fractional-Order Elements (FOEs) and their applications. (February 2019) - Shah, Zaid Mohammad; Kathjoo, Mujtaba Yousuf; Khanday, Farooq Ahmad; Biswas, Karabi; Psychalinos, Costas
Abstract: Fractional-Order circuits and networks being a widely researched field lags in its development due to the non-availability of its basic building block i.e. Fractional-Order Element (FOE). The FOE besides being compact and having wide frequency range should also be integrable with the Integrated Circuit (IC). In this paper, a detailed survey of single and multi-component FOE implementations has been carried out. The survey implies that a single component FOE is more suited for integration with the conventional circuitry but a market fit device is still a topic of research. Some future prospects and areas of research for the implementation of FOE have also been indicated in the paper. In addition, a survey of applications of single and multi-component FOE has also been included in the paper.